أثر الإستثمار في رأس المال البشري في تعزيز التحول الرقمي في البنك الوطني الجزائري Bna - كويسي توفيق; عيشوش عواطف (جامعة الوادي University of Eloued, 2024)
The research was designed to underscore and delineate the influence that human capital investment has on advancing the digital transformation within the Algerian National Bank. The study examined the relationship and effects of the independent variable: investment in human capital (in terms of polarization, development, and conservation), on the dependent variable of digital transformation. A descriptive analytical approach was utilized for this examination. The primary method of data gathering involved distributing questionnaire forms to 40 relevant employees, and the data obtained were analyzed using SPSS version 25. The findings of the research indicated a significant correlation and impact of human capital investment (specifically within the governorate) on the digital transformation at the National Bank of Algeria.
Impact of human capital investment on the promotion of digital transformation in the Algerian National Bank BNA
Keywords: رأس المال البشري; إستثمار رأس المال البشري; التحول الرقمي; .، الادراة الإلكترونية; البنك الوطني الجزائريBNA.; human capital; investment in human capital; electronic management; digital transformation; National Bank of Algeria